Antioxidant Properties of Mandai Prepared at Different Fermentation Time - Abdul Kadir, Nurul Aina Natasha; Sabran, Siti Fatimah (Enhanced Knowledge in Sciences and Technology, 2025)
Mandai is a fermented product made from the inner skin of chempedak (Artocarpus integer). The influence of traditional fermented food as functional food has significantly increased due to its health-promoting properties. However, there is still a lack of studies on the antioxidant properties of Mandai prepared at different fermentation times. This study is significant as fermentation time is a critical factor in determining the antioxidant properties of Mandai. This study investigates the antioxidant properties of Mandai, a traditional fermented food prepared at different fermentation times. The primary objective is to evaluate the antioxidant properties of Mandai prepared at different fermentation times and identify the optimal fermentation time for maximizing the antioxidant properties of Mandai. The samples of Mandai were prepared in the laboratory by using the inner skin of Artocarpus integer (chempedak). The samples were then fermented for 0, 7, 14, 21, and 28 days. The antioxidant properties of Mandai were measured using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and Ferric Reducing Antioxidant Power (FRAP) assay. The DPPH assay showed that the antioxidant activity was highest at 58.63±5.29% after 7 days of fermentation, compared to 52.06±0.88% at day 0. The activity then decreased to 46.71±0.14% on day 14, 32.91±1.53% on day 21, and 34.64±6.74% on day 28. In contrast, the FRAP assay demonstrated the highest antioxidant activity (62.13±1.59%) at 14 days of fermentation, starting from 29.74±1.52% at day 0, and followed by a reduction to 48.51±2.60% at day 21 and 32.67±3.42% at day 28. These findings suggest that 7 days of Mandai fermentation is recommended as the optimal fermentation time as it demonstrated positive effects from both DPPH and FRAP assays. In conclusion, the result showed that Mandai prepared at different fermentation times highlight the valuable source of antioxidants. Future studies should standardize other fermentation condition, investigate the effect of temperature and pH and identify specific bioactive compounds contributing to antioxidant activity as well as the biochemical changes during fermentation.